Compulsory insurance against natural disasters as collateral in construction with the Algerian legislation - Chaibbacha, Karima Ahmed (Journal of Risk and Crisis Management, 2021)
This study aimed to identify the issue of insurance provisions against natural disasters in general and its compulsory nature in the field of construction in particular, on the basis of the role it plays in preserving individuals’ real estate properties built, while highlighting the importance of the existence of this type of compulsory and participatory insurance in bearing losses And generalize it while encouraging and spreading the culture of insurance. And based on the objectives pursued by this study and to encompass the various aspects of the topic, we used the descriptive and analytical approach as two pillars in this study by working to collect information about all concepts related to insurance in general, with identifying accidents that constitute natural disasters, as well as analyzing the reality of the intervention of the Algerian legislator based on Basically, the insurance law. Therefore, the legal texts issued in this regard were relied upon as a source for this topic. Depending on the binary division of the study, into two main axes, and each axis is divided into two sub-axes. As for the basic division, it is represented in: Standing on the nature of compulsory insurance on natural disasters according to the Algerian legislation, so exposure to the effects of insurance on natural disasters. And through this research, we have reached as a whole: Natural disaster insurance is a system based on its content on the idea of ​​social solidarity. And that it bears a compulsory and participatory nature in bearing losses, and it is linked to the declaration of natural disaster. The general rule in insurance against natural disasters is optional, but as an exception to this, some insurances are required by the legislator to conclude them and subscribe with the insurance company on natural disasters. Compulsory insurance for natural disasters in Algeria remains an economic act par excellence. And based on these presented results, some recommendations were made, including: The necessity of activating the control over the extent of compliance with this type of insurance despite its legally binding because individuals in reality do not comply with that except in front of the notary when selling or renting the built property. Therefore, violators of this obligation shall be punished with financial fines. And doubling it in the case of recidivism, and the establishment of a construction insurance fund to compensate for damages in the event of insolvency of insurance companies.